Pendidikan Agama Islam Integratif Perspektif Gus Dur di Era Digital - Irsyad, Mohammad; Basri, Basri; Barizi, Ahmad (Sekolah Tinggi Ilmu Tarbiyah Al Mubarok Bandar Mataram, 2025)
The chronic disease of scientific dichotomy seems to still infect some activists of Islamic religious education. This results in scientific discrimination in the form of extreme separation between